Identifikasi dan Karakterisasi Sumber Daya Genetik Buah-buahan Lokal di Kabupaten Jembrana - PRATAMA, I PUTU DIAN; GUNADI, I GUSTI ALIT; DARMAWATI, IDA AYU PUTRI; RAI, I NYOMAN (Agrotrop : Journal on Agriculture Science, 2018)
Identification and Characterization of Plant Genetic Resources Local Fruits in Jembrana. Fruits are one source of nutritious food that have diverse functions such as: source of vitamins, minerals, and fiber needed in the daily menu. Fruits are used as community consumption, tourism needs, inter island trade, as well as for religious activities, even thoughthere are local fruit are used in “usadha”by generations. Jembrana Regency has various types of fruits. This study aims to identify the genetic resources of fruits in Jembrana Regency. This research was conducted in five stages: (1) collected secondary data, (2) surveyed the types of genetic resources and their distributions, (3) identification of morphological and agronomiccharacters, (4) determined superior fruit, and (5) compiled geographic map the distribution of genetic resources of local fruits. The result of research found 38 species and 53 sub-types of local fruit plants, with 6 types of superior fruit, 12 type of rare fruit, 17 types of fruit for upakara, and 9 types of fruits for medicine. Based on the survey conducted in Jembrana District, 41 geographical distribution maps of local fruits can be compiled.